Stress control and bicuspidization - Devi, W. Priya; Chirom, Babina; Mushahary, Tharaina (International Journal Of Community Medicine And Public Health, 2023)
Mandibular molars being the first teeth to erupt in the oral cavity have high caries susceptibility index, deprivation in its maintenance may lead to serious problem like furcation involvement. Recent advances in dentistry and the desire of patients to maintain their dentition, have lead to treatment of teeth that once would have been removed. Bicuspidization is a procedure in which separation of distal and mesial roots of mandibular molar with their coronal portion are done. This separation helps to eliminate the existing furcation and ensure effective oral hygiene maintenance. The mandibular molar teeth with severe bone loss at interradicular area may be retained of their roots. In this case report, a basic procedure of bicuspidization of right first mandibular molar followed by prosthetic treatment has been presented.